Analisis Pengaruh Rasio Likuiditas, Leverage, Aktivitas Dan Profitabilitas Terhadap Return Saham (Studi Kasus Terhadap Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2019) - Ratma Ana Tasya; Muhammad Agus Salim; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe era of globalization, companies are required to compete globally. Therefore, companies must compete to improve the company's performance in order to compete with the company in order to increase its existence. This is done solely to attract investors who will invest in the company. A company must provide financial information its company provides financial reports that are issued annually. Investment is an activity that involves funds in assets that are intended to get the expected return (return). One investment that is often found is stocks. Investors need to have benchmarks in order to know whether he will get a profit if investing or investing in a company. Therefore the usual method used in corporate valuation is the basis of company judgment because the basic consideration of explaining the strength and tendency of increasing the company's finances is the financial ratio. Through financial ratios the company can compare the development of a company from time to time to determine the trends that are happening. Second, we can compare the company's financial ratios with other companies that are still engaged in an industry that is relatively equal to a certain period. As a ratio commonly used in analyzing fundamentals are Liquidity, Leverage, Activity and Profitability Ratios. Therefore, the researchers took the title Analysis of the Effect of Riku Liquidity, Leverage, Activity and Profitability on Stock Return Case studies of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2019. Keywords: Ratio Likuiditas, Leverage, Aktivitas, Profitabilitas and Return Saham.